PENGARUH AKTIVASI KOLAGEN PADA PLATELET-RICH PLASMA TERHADAP PROLIFERASI FIBROBLAS LIGAMEN PERIODONTAL (KAJIAN IN VITRO) - , PATI TANGSUPATI, drg. Kwartarini Murdiastuti, Sp.Perio (K), Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Platelet-Rich Plasma (PRP) is a high concentration of platelet preparations which is obtained by centrifugation of peripheral blood. PRP release growth factors that have a regulatory effect on biological processes at the cellular level, such as cell migration, cell proliferation, cell adhesion, cell differentiation, and tissue morphogenesis. Platelets will only release growth factors with other cytokines from the granules when activated. This study would use collagen to activate the PRP. The aimed of this study was to evaluate benefits of collagen in PRP activation and the collagen-activated PRP storage. The primary fibroblasts of periodontal ligament were obtained from premolar removed for orthodontic treatment. PRP obtained from 100 ml of blood donors using double centrifugation methods. PRP activated with collagen and incubated for 24 hours, 48 hours, 72 hours and 168 hours, after which the lysate was taken. Fibroblasts were divided into seven groups, one group unstimulated count as negative control, one group was stimulated with PRP lysate alone, five other groups each stimulated with PRP+collagen lysates that had been incubated for 24 hours, 48 hours, 72 hours and 168 hours. MTT Assay were than performed after one and three days. The results showed the proliferation rate of fibroblasts group stimulated with PRP + collagen lysate higher than the group stimulated with PRP. Collagen-activated PRP stored for 7 days at 4 Â° C could increase the proliferation rate. Conclusion : The activation of rat tail collagen as well as collagen sponges in PRP may increased the rate of proliferation of periodontal ligament fibroblast and the stored collagen-activated PRP may also increased the proliferation rate.